Accelerated protein synthesis via one–pot ligation–deselenization chemistry - Mitchell, Nicholas J.; Sayers, Jessica; Kulkarni, Sameer S.; Clayton, Daniel; Goldys, Anna M.; Ripoll-Rozada, Jorge; Barbosa Pereira, Pedro José; Chan, Bun; Radom, Leo; Payne, Richard J. (Elsevier, 2017)
Peptide ligation chemistry has revolutionized protein science by facilitating access to synthetic proteins. Here, we describe the development of additive-free ligation-deselenization chemistry at β-selenoaspartate and γ-selenoglutamate that enables the generation of native polypeptide products on unprecedented timescales. The deselenization step is chemoselective in the presence of unprotected selenocysteine, which is highlighted in the synthesis of selenoprotein K. The power of the methodology is also showcased through the synthesis of three tick-derived thrombin-inhibiting proteins, each of which were assembled, purified, and isolated for biological assays within a few hours. The methodology described here should serve as a powerful means of accessing synthetic proteins, including therapeutic leads, in the future.